Balancing elderly care and employment in Germany - Wolfgang Keck; Chiara Saraceno (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 2009)
In this report, we investigate the situation of workers who also care for an elderly parent in Germany. The study is based on qualitative, in depth interviews with care givers who are at least part time employed. The interviews aimed at detecting constrains and resources available to workers with caring responsibilities in the second half of their working life to deal with their multiple responsibilities and demands on their time and attention. This report is one of a series of national reports on the same issue, which are all part of the project "Workers under pressure and social care" (WOUPS) supported by the French ministry of labour (MIRE) and by the French Agence Nationale de la Recherche (ANR), coordinated by the department of Ecole nationale de la santé publique at the University in Rennes. Towards this project, we also provided a report on the institutional framework of the German long-term care system, which we only synthetically summarize in the first part of this. The outline of the report is as follows: The first section points to the relevance of balancing employment and informal elderly care in Germany and highlights the peculiarities of elderly care compared to child care. The second section, after a synthetic description of the key elements of the German long term care system, presents an overview, based on existing survey data, of the incidence and characteristics of workers having caring responsibilities towards an adult family member in Germany. The third section describes our sample of carers and evaluates its representativity and possible biases. In the fourth section, we discuss different patterns of work/care arrangements. In the fifth chapter, we analyse the tensions arising in these arrangements with regard both to caring and to gainful employment, paying attention to constrains, but also to the - human and emotional - resources carers are able to mobilize in the various situations. In the following two sections, the conciliation, or balancing, perspective is broadened to include family and friendship relationships as well as time for one's own. In the concluding section, we highlight the most crucial aspects which put care givers in employment under pressure and we describe measures that might ease their situation.
Keywords: 300; Pflegedienst; Familie; Arbeitszeit; Freizeit; Familie-Beruf; Deutschland